2013
DOI: 10.3389/fnsys.2013.00092
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural changes throughout the auditory system following congenital and early-onset deafness: implications for hearing restoration

Abstract: The absence of auditory input, particularly during development, causes widespread changes in the structure and function of the auditory system, extending from peripheral structures into auditory cortex. In humans, the consequences of these changes are far-reaching and often include detriments to language acquisition, and associated psychosocial issues. Much of what is currently known about the nature of deafness-related changes to auditory structures comes from studies of congenitally deaf or early-deafened an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 197 publications
(277 reference statements)
2
42
0
1
Order By: Relevance
“…A number of studies have suggested that hearing loss during early development (even if temporary) can greatly influence the development of the central auditory system (Xu et al, 2007;Hatano et al, 2012;Butler and Lomber, 2013;Polley et al, 2013). Interestingly, exposure to noise on P14d in rats, which was a time point used in the present study, has a huge impact on startle responses and frequency coding differing from the effects of noise exposure in adult animals Suta et al, 2015).…”
Section: Discussionmentioning
confidence: 68%
“…A number of studies have suggested that hearing loss during early development (even if temporary) can greatly influence the development of the central auditory system (Xu et al, 2007;Hatano et al, 2012;Butler and Lomber, 2013;Polley et al, 2013). Interestingly, exposure to noise on P14d in rats, which was a time point used in the present study, has a huge impact on startle responses and frequency coding differing from the effects of noise exposure in adult animals Suta et al, 2015).…”
Section: Discussionmentioning
confidence: 68%
“…The gradual decrease in size of SGNs (Table ) indicates progressive degeneration of the auditory nerve with time after cochlear damage. Thus, our model reproduces an abrupt cessation of peripheral synaptic auditory input, accompanied by progressive structural damage of first order neurons and their central synapses (Butler & Lomber, ; Wang, O'Donohue, & Manis, ). Animal models of deafness induced by cochlear mechanical lesion have been previously used to investigate post‐lesion plasticity in the auditory pathway (Vale & Sanes, ; Illing, Kraus, & Meidinger, ; Rubio, ; Alvarado, Fuentes‐Santamaría, & Henkel, ).…”
Section: Discussionmentioning
confidence: 86%
“…(Interestingly, Kamal et al also found that several of the measured changes showed reversal after returning the young rats to a quiet environment.) Such studies suggest that many of the findings regarding noise-induced hearing loss have implications for normal aging [50-52]. …”
Section: Changes To the Auditory System In Adult Agingmentioning
confidence: 99%